The Qur'an's Perspective on the Phenomenon of Cyberbullying on Social Media: Contextual Approach - Isna Fitri Choirun Nisa’; Abdul Fatah (MAQOLAT: Journal of Islamic Studies, 2025)
This study examines the phenomenon of cyberbullying on social media through a contextual approach, focusing on the interpretation of relevant Qur'anic verses and their application to modern digital behavior. The research identifies that the majority of cyberbullying cases on platforms like Instagram, Facebook, X (formerly Twitter), and TikTok take the form of verbal harassment, including flaming, impersonation, trickery, and denigration. The research method is library research, with primary data sourced from the Qur'anic term “sakhara” (humiliating or mocking), This term is further interpreted using both classical and contemporary exegeses. The paradigm used is contextual hermeneutic approach. The results of this study show that: 1) Cyberbullying on social media is found on Instagram, Facebook, X, and TikTok. The cyberbullying patterns in the majority of social media are verbal harassment with the aim of insulting and humiliating someone. 2) The term sakhara is the root word that is closest to the meaning of cyberbullying because it has insulting and degrading meanings. The the word sakhara is mentioned 32 times in the Qur'an. Three main verses are selected to be discussed: Q. S. al-Hujurat [49]:11, Q. S. at-Taubah [9]:79, and Q.S. al-An’am [6]:10. The verses reveal a clear prohibition against mocking and degrading others. These verses highlight the importance of maintaining respect and dignity, even in the face of mockery, and the need for resilience and faith in the face of such challenges. The study concludes that insults and mockery should not be normalized, as they can lead to harmful consequences, including the emergence of cyberbullying, which has significant negative effects on individuals.